2015
DOI: 10.3906/sag-1404-14
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester protects lung alveolar epithelial cellsfrom cigarette smoke-induced damage

Abstract: Background/aim: To evaluate the influence of caffeic acid phenethyl ester (CAPE) on cigarette smoke (CS)-induced cell damage, oxidative stress, and inflammation in human alveolar epithelial cells.Materials and methods: A549 alveolar epithelial cells were divided into control, CS exposure, CAPE, and CS+CAPE treatment groups. Undiluted CS-exposed medium (100%) and three dilutions (50%, 25%, and 10%) of CS-exposed media were applied to cultured A549 cells, which were analyzed after 3 h of incubation. Viability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…CAPE has been reported to suppress NO production and iNOS activity in different in vivo and in vitro models. [31][32][33]…”
Section: Discussionmentioning
confidence: 99%
“…CAPE has been reported to suppress NO production and iNOS activity in different in vivo and in vitro models. [31][32][33]…”
Section: Discussionmentioning
confidence: 99%
“…Its already has been demonstrated that CAPE could protect the cells from various damages such as CS or oxidative stressors. [22][23][24][25] However, the underlying mechanisms have not been sufficiently demonstrated. Although low levels of CAPE protects lung alveolar cells from damages or inflammation, higher concentrations could be apoptotic or cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…[22] The study groups are follows: C, control (untreated); CS, tobacco cigarette smoke-exposed group; CAPE, caffeic acid phenethyl ester applied; +CAPE, CS exposed-CAPE treated cells.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Introduction. Among urgent problems of health care worldwide, a signifi cant place is occupied by exogenous allergic alveolitis (EAA), which attracts attention of internists and allergists and is associated with a high incidence of this pathology in the structure of allergic diseases and an increase in severe complicated forms of this disease [1][2][3][4]. Currently, EAA is regarded as the pathology, associated with the risk of disability, manifested by chronic respiratory insuffi ciency, pulmonary heart or pneumosclerosis [5].…”
mentioning
confidence: 99%